Pilot Randomized Trial of a Pharmacy Intervention for Older Adults with Cancer. (19th October 2018) - Nipp, Ryan D.; Ruddy, Margaret; Fuh, Charn‐Xin; Zangardi, Mark L.; Chio, Christine; Kim, E. Bridget; Li, Barbara Kong Mui; Long, Ying; Blouin, Gayle C.; Lage, Daniel; Ryan, David P.; Greer, Joseph A.; et al.
Abstract: Background: Oncology clinicians often struggle with managing medications and vaccinations in older adults with cancer. We sought to demonstrate the feasibility and preliminary efficacy of integrating pharmacists into the care of older adults with cancer to enhance medication management and vaccination administration. Methods: We randomly assigned patients aged ≥65 years with breast, gastrointestinal, or lung cancer receiving first‐line chemotherapy to the pharmacy intervention or usual care. Patients assigned to the intervention met with a pharmacist once during their second or third chemotherapy infusion. We obtained information about patients' medications and vaccinations via patient report and from the electronic health record (EHR) at baseline and week 4. We determined the number of discrepant (difference between patient report and EHR) and potentially inappropriate (Beers Criteria assessed by nonintervention pharmacists blinded to group assignment) medications. We defined the intervention as feasible if >75% of patients enrolled in the study and received the pharmacist visit. Results: From January 17, 2017, to October 27, 2017, we enrolled and randomized 60 patients (80.1% of patients approached). Among those assigned to the intervention, 96.6% received the pharmacist visit. At week 4, intervention patients had higher rates of acquiring vaccinations for pneumonia (27.6% vs. 0.0%, p = .002) and influenza (27.6% vs. 0.0%, p = .002) compared with usual care. Intervention patients had fewer discrepant (5.82 vs. 8.07, p = .094) and potentially inappropriate (3.46 vs. 4.80, p = .069) medications at week 4, although differences were not significant. Conclusion: Integrating pharmacists into the care of older adults with cancer is feasible with encouraging preliminary efficacy for enhancing medication management and improving vaccination rates. Implications for Practice: Results of this study showed the feasibility, acceptability, and preliminary efficacy of an intervention integrating pharmacists into the care of older adults with cancer. Notably, patients assigned to the intervention had fewer discrepant medications and were more likely to acquire vaccinations for pneumonia and influenza. Importantly, this work represents the first randomized controlled trial involving the integration of pharmacists into the outpatient oncologic care of older adults with cancer. In the future, a larger randomized trial is needed to demonstrate the efficacy of this care model to enhance medication management and improve vaccination outcomes for older patients with cancer. Abstract : Medication management and vaccinations are particularly challenging in an older cancer population, and incorporating clinical pharmacists into the cancer care of older patients represents a potential strategy to enhance clinical outcomes for the geriatric oncology population. This article reports on the feasibility and efficacy of integrating pharmacists into the care of older adults with cancer to improve medication management and vaccination administration.